The Effectiveness of School Leaders' Leadership in National Special Education School in Kuala Lumpur - Shamim Samsuddin; Muhammad Faizal A Ghani; Abd. Muhith (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2023)
Every school needs a comprehensive plan to produce well-rounded students who meet their physical, emotional, spiritual, intellectual, and social needs. Therefore, the success of a school is determined by the cohesive cooperation between the school community and the stakeholders managed by the school leader. However, a research study found that leaders in special education schools still need to understand the necessary leadership strategies to implement. Failure to do so can result in weak or ineffective leadership. Hence, this study analyzed the leadership level of school leaders in special education schools in Kuala Lumpur. The data was obtained through a quantitative method, which involved conducting a survey using questionnaires as the research instrument. The questionnaire was distributed to 66 special education school teachers. The results showed that the leadership level of special education school leaders for the domain of creating a conducive school environment (overall min: 2.70), improving the competence of school members (overall min: 2.48), and creating partnerships and networking (overall min: 2.63) was at a modest level. Therefore, the stakeholders in the Regional Education Office, State Education Department, and the Malaysian Ministry of Education need to collaborate and channel their efforts towards raising the leadership capabilities of special education school leaders to the highest possible level. It will enable the implementation of the PPPM 2013-2025 goal to place high-achieving leaders in every school.